Evaluation of Type of Impression Technique Used in Tooth Supported Full Mouth Rehabilitation - A Retrospective Study - REDDY, DR. M.SAI TEJA; AHMED, DR. NABEEL; SASANKA, DR. KEERTHI (The journal of contemporary issues in business and government, 2021)
The aim of this study was to retrospectively evaluate the type of impression technique used by various dental students. A total of 98 data entries were taken, duplicate and missing entries were omitted. So a total of 63 entries were evaluated. The data was collected from patient records in Saveetha Dental College, over a period of one year. . The evaluation was based on the type of impression technique used by various dental students. The results of the study were subjected to statistical analysis. Data analysis was done using SPSS software version 23.0. Chi- square test and frequency evaluation was done to evaluate the most frequently used impression technique in FMR. It was found that more than 92% of dental students preferred to use double stage putty wash technique with a (P-value - .743) The present study concluded that most of the dental students preferred to use double stage putty wash impression technique for their dental treatment